Analisa Konsep Ide Bisnis Makanan Kucing Dari Bahan Organik “Mimeow” - Wirren Chang; Renny Christiarini; Agnes Doraresta Khatarina Tokan; Delfina Muthia Sabella; Dewi Dewi; Mardiana Ng; Serina Serina (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
MiMeow is a business that emerged from a student idea. Mimeow is a business that produces cat food, which is in the form of wet food. The products that researchers produce focus on raising funds to help hungry feral cats. In this study, we will discuss project integration, project scope management, project time management, project cost management, project quality management, project human resource management, project communication management, project risk management, project procurement management and project stakeholder management from "Mimeow".